THEORETICAL FOUNDATIONS OF GRIGORY NADGI’S RESEARCH ON SONG FOLKLORE - Шталь, Іванна; Марчун, Оксана; Коломицева, Марія (SWorldJournal, 2022)
The article deals with the main folklore interests of the authoritative Ukrainian folklorist of the 20th century Grigory Nudga. Attention is paid to the theoretical substantiation of the problem posed by the scientist of the spread of Ukrainian folk son